A new species of the stingless bee Trichotrigona (Hymenoptera: Apidae, Meliponini) - Pedro, Silvia R. M.; Cordeiro, Guaraci Duran (Zootaxa, 2015)
Trichotrigona camargoiana sp. nov. from Candeias do Jamari, Rondônia, Brazil is described and illustrated, along with nesting and behavior, as the second species of the rare and unusual genus Trichotrigona Camargo & Moure, 1983. The new species differs from T. extranea Camargo & Moure, 1983 by having plumose setae on the face and mesepisterna, wing setae predominantly yellow and black metatibia. The diagnosis for Trichotrigona is updated. As believed for T. extranea, T. camargoiana sp. nov. apparently does not store food and is a cleptobiotic social bee associated with Frieseomelitta.